SYTO9 and SYBR GREEN1 with a high-resolution melting analysis for prenatal diagnosis of β0-thalassemia/hemoglobin-E - Sakorn Pornprasert (2018)
The Β0-thalassemia/Hb-E causes a wide range of severe conditions. A high medical cost is incurred in severe cases. Thus, the prevention of new cases of Β0-thalassemia/Hb-E is required. The aim of this study is to use the SYTO9 and SYBR GREEN1 high-resolution melting (HRM) analysis for prenatal diagnosis of Β0-thalassemia/Hb-E. DNA samples were extracted from amniotic fluid or cord blood of 11 pregnancies whose fetuses were at risk for Β-thalassemia/Hb-E. PCR products from multiplex amplification refractory mutation system PCR for the detection of β0-thalassemia mutations at codons 17(A>T), 41/42(-TCTT), and 71/72(+A) and from amplification refractory mutation system PCR for the detection of Hb-E were characterized by SYTO9 HRM analysis. Moreover, β0-thalassemia 3.5- kb deletion was detected using real-time PCR with SYBR GREEN1 HRM analysis. Seven of 11 fetuses (64%) were diagnosed as β0-thalassemia/Hb-E (4 fetuses with mutation at codon 17, 2 with mutation at codon 41/42, and 1 with 3.5- kb deletion). Results from HRM analysis were completely consistent with those from fetal blood samplings analyzed at the time of delivery or pregnancy termination using HPLC. Therefore, the HRM analysis is easy to use. It is simple, flexible, non-destructive and has superb sensitivity and specificity. This approach might facilitate the laboratory diagnosis and genetic counseling for regions with a high prevalence ofβ0-thalassemia/Hb-E. © 2010 John Wiley & Sons A/S.